The Slang Translation of Game “Honkai : Star Rail” by Mihoyo - Widiyantari, Yunita; Himawan Satria Sakti, Dyanizieus (University of Surakarta, 2026)
Slang, or colloquial language, is a linguistics phenomenon that often occurs in daily conversations. It is spread into content across various forms of entertainment media such as music, memes, and games. The study analyzes the use of slang in the translation of the game titled “Honkai: Star Rail.” It is a qualitative research with Triangulation data employed to validate the data by using raters. The translation quality was analyzed in terms of accuracy, acceptability, and readability. The results show that the accuracy of 80.25% data is classified as Accurate; 18.52% data is classified as Less Accurate; and only 1.23% is classified as Not Accurate. The acceptability results show that 83.95% data is classified as Acceptable; 16.5% data is classified as Less Acceptable; and none with a score of 1 that is considered as Not Acceptable. Meanwhile, the readability results show that 85.19% data is classified as Highly Readable; 12.35% data is classified as Moderate Readable; and 2.46% data is classified as Low Readable. The score of the translation quality indicates that the translators successfully provided the best equivalent for the translations of this game in those three translation quality aspects.